1974
DOI: 10.1002/bjs.1800611214
|View full text |Cite
|
Sign up to set email alerts
|

Racial incidence of postoperative deep vein thrombosis in South Africa

Abstract: Postoperatiue deep uein thrombosis is considered to be rare in non-Europeans (Burkitt, 1972). The '"I fibrinogen test, Doppler ultrasound and venography were used to determine the true incidence of' postoperative deep vein thrombosis in a South African population. The results show that the European, Coloured, African nnd Indian patients were all at a similar high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1975
1975
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…However, mortality data obtained by WHO must be interpreted with caution, since possible sources of bias, such as variations in coding practices, limitations in the number of secondary diagnosis coded, and diagnoses not definitely confirmed may be present. WHO Bulletins do not provide TE death rates for Africans and furthermore results of clinical studies are in conflict (24)(25)(26). Nevertheless, autoptic studies, which represent the gold standard for diagnosis of pulmonary embolism, clearly demonstrated a low prevalence of TE in Africans (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality data obtained by WHO must be interpreted with caution, since possible sources of bias, such as variations in coding practices, limitations in the number of secondary diagnosis coded, and diagnoses not definitely confirmed may be present. WHO Bulletins do not provide TE death rates for Africans and furthermore results of clinical studies are in conflict (24)(25)(26). Nevertheless, autoptic studies, which represent the gold standard for diagnosis of pulmonary embolism, clearly demonstrated a low prevalence of TE in Africans (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…A further autopsy-based study in Japan found a significantly lower frequency of PE compared to matched cases in Boston (USA) (Gore et al, 1964). In contrast, a small study (100 patients) undertaken in South Africa investigating post-operative DVT utilising both radio-isotope and Doppler ultrasound imaging in patients undergoing major surgery found high rates of asymptomatic DVT of up to 50% in non-Europeans, equal to the rate detected in Europeans (Joffe, 1974). This provided initial evidence to challenge the perception that VTE was rare in non-Caucasians and suggested that low rates reported in other ethnic groups were possibly due to under-diagnosis and retrospective study design.…”
Section: Early Reports Suggesting a Low Incidence In Non-caucasian Pomentioning
confidence: 92%
“…Age [31][32][33][34][35][36][37][38]53,69,102,260 Moderate Obesity [32][33][34][35]37,102,133,260 Minor Ethnicity 31,42,263 Minor Immobilization 34,41 Moderate Previous VTE 31,34,41,102 Severe Estrogen therapy 53,176 Minor Inherited thrombophilia 209,250,251,260 Severe Malignancy 32,34,35,37,53,[99][100][101] Moderate Heparin-inudced thrombocytopenia 234 Severe…”
Section: Risk Factors Severitymentioning
confidence: 99%